Politics and Census in Nigeria: Challenges and the Way Forward - NWACHUKU, Azuka (LPPM Universitas Malikussaleh, 2023)
Population is very vital to the government for nation building of a country especially, Nigeria. Nigerias population has been contentious and politicized since colonial times. Census statistics embodies an essential database prerequisite for measuring the physical and social well-being of a nations population. Hence, for any country to realize its development potentials, it requires a comprehensive population database support to guide its socio-economic programs, planning and implementation. The fusses in Nigeria census steered the cancellation of the 1962 general population census which was repeated in 1963.The Population of an area is considered a political weapon, a condition desiderata for provision of amenities, infrastructure and in fact, guides wealth allocations and fiscal planning. Regrettably, Nigeria is yet to produce an acceptable and satisfactory demographic data for infrastructural development and nation building. Scholars of Nigerian history appear not to have paid adequate attention to nation building in Nigeria as a result of inaccurate population database. Hence, it is a perception of issues of politics and population census this paper tend to address. Qualitative research methodology was adopted for effective analyses. The paper concluded that inherent contemporary issues have continued to defeat the main aim of population census as an instrument for strategic planning and sustainable development. Lack of accurate census figures has contributed to Nigerias policy summersault and under development. It is unfortunate that in this 21st century Nigeria still does not have effective and reliable census data due to the fact that politicization, Falsification of population census result, religion rivalry, ethnicity stimulation and fluctuation of period of conducting census serves as a controlling force against accuracy of population census figures.